Electrocardiographic abnormalities in elite high school athletes: comparison to adolescent hypertrophic cardiomyopathy. Issue 2 (4th January 2016) - Thompson, Alex J; Cannon, Bryan C; Wackel, Philip L; Horner, Justin M; Ackerman, Michael J; O'Leary, Patrick W; Eidem, Benjamin W; Johnson, Jonathan N
Abstract : Background: In athletes, ECG changes from physiological cardiac remodelling are common but can overlap with findings from a pathological disorder. We compared ECG findings in a group of elite high school athletes to a cohort of adolescents with hypertrophic cardiomyopathy (HCM). Methods/results: We prospectively performed 15-lead ECGs and echocardiograms in 147 elite high school athletes. Student-athlete ECGs were compared in blinded fashion to ECGs of 148 adolescents with HCM of similar age and ethnicity. Standard ECG hypertrophy criteria and established expert opinion guidelines (European Society of Cardiology, ESC and Seattle criteria) were analysed. All student-athletes had normal echocardiograms. Overall, 77/147 (52%) of student-athletes met standard ECG criteria for ventricular hypertrophy compared to 126/148 (85%) adolescents with HCM (p<0.0001). There were 112/148 (76%) adolescents with HCM who had pathological Q-waves, T-wave inversion and/or ST-segment depression compared to 1/147 (1%) athletes (p<0.0001). Most patients with HCM (84%, 124/148) had ≥1 abnormal ECG finding(s) according to Seattle criteria, compared to 1% of student-athletes (2/147). Similarly, 130/148 (88%) patients with HCM met group-2 ESC criteria (abnormal), compared to 36/147 (24%) student-athletes (p<0.0001). Conclusions: Over 50% of elite high school athletes with echocardiographically confirmed normal hearts satisfied standard voltage criteria for ventricular hypertrophy. Pathological Q-waves, T-wave inversion or ST-segment depression were most helpful in distinguishing adolescents with HCM from normals. Both ESC and Seattle criteria successfully stratified the student-athlete and HCM cohorts, however each had a false-negative rate >10% for the HCM cohort. The Seattle criteria demonstrated a significantly lower false-positive rate (1%) than the ESC criteria (24%).